Understanding accountability in democratic governance - Papadopoulos, Ioannis, 1960- (Cambridge elements. Elements in public policy, 2023)
This Element comprehensively scrutinizes the key issue of the accountability of policy-makers in democratic governance. The electoral punishment of the incumbents, parliamentary control of the government, and sanctions in the case of administrative misconduct or negligence are the most visible manifestations of accountability in politics. However, the phenomenon is much more complex, and fully understanding such a multifaceted object requires bridging bodies of work that usually remain disjointed. This Element assesses the effectiveness of vertical accountability through elections and how interinstitutional accountability operates in checks-and-balances systems, along with the growing role of the courts. It evaluates how the accountability of the bureaucracy has been affected by managerial reforms and different governance transformations. It also scrutinizes to what extent mediatization and policy failure boost accountability, before zooming in on the feelings and reactions of those who are held accountable. This title is also available as Open Access on Cambridge Core.